Creation and Worldwide Utilisation of New COVID-19 Online Information Hub for Genetics Health Professionals, Patients and Families - Tobias, Adam P.; Berg, Jonathan; Cetnarskyj, Roseanne; Miedzybrodzka, Zosia; Porteous, Mary E.; Tobias, Edward S. (Frontiers in Genetics, 2021)
The current COVID-19 pandemic has unfortunately resulted in many significant concerns for individuals with genetic disorders and their relatives, regarding the viral infection and, particularly, its specific implications and additional advisable precautions for individuals affected by genetic disorders. To address this, the resulting requirement for guidance and information for the public and for genetics professionals was discussed among colleagues nationally, on the ScotGEN Steering Committee, and internationally on the Education Committee of the European Society of Human Genetics (ESHG). It was agreed that the creation of an online hub of genetics-related COVID-19 information resources would be particularly helpful. The proposed content, divided into a web page for professionals and a page for patients, was discussed with, and approved by, genetics professionals. The hub was created and provided online at www.scotgen.org.uk and linked from the ESHG’s educational website for genetics and genomics, at www.eurogems.org. The new hub provides links, summary information and representative illustrations for a wide range of selected international resources. The resources for professionals include: COVID-19 research related hubs provided by Nature, Science, Frontiers, and PubMed; clinical guidelines; the European Centre for Disease Prevention and Control; the World Health Organisation; and molecular data sources including coronavirus 3D protein structures. The resources for patients and families include links to many accessible sources of support and relevant information. Since the launch of the pages, the website has received visits from over 50 countries worldwide. Several genetics consultants have commented on usefulness, clarity, readability, and ease of navigation. Visits have originated most frequently in the United Kingdom, Kuwait, Hong Kong, Moldova, United States, Philippines, France, and Qatar. More links have been added since the launch of the hub to include additional international public health and academic resources. In conclusion, an up-to-date online hub has been created and made freely available for healthcare professionals, patients, relatives and the public, providing categorised easily navigated links to a range of worldwide resources related to COVID-19. These pages are receiving a rapidly growing number of return visits and the authors continue to maintain and update the pages’ content, incorporating new developments in this field of enormous worldwide importance.